2017
DOI: 10.1111/hsc.12485
|View full text |Cite
|
Sign up to set email alerts
|

Combining informal care and paid work: The use of work arrangements by working adult-child caregivers in the Netherlands

Abstract: An increasing number of people combine paid work with the provision of informal care for a loved one. This combination of work and care may cause difficulties, necessitating adaptations at work, i.e. work arrangements. The present study explores what types of work arrangements are used by working caregivers, and which caregiver, care and work characteristics are associated with the use of these work arrangements.Within the Lifelines Informal Care Add-on Study (Lifelines ICAS), data on 965 Dutch informal caregi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 37 publications
4
20
2
1
Order By: Relevance
“…Moreover, and although research has found contradictory findings [15], a large percentage of studies found that caring for a dependent person is related to a series of burdens that often takes them to their physical, psychological and emotional limits [1517], impacting the whole family system [15]. The responsibilities imposed by the caregiving situation may interrupt social life, activities or even work, which may be challenging [18]. For instance, some studies report that caregiving is usually associated with a deterioration in the quality of life [5, 6, 19, 20], higher levels of depression symptoms [5, 19, 21, 22], greater financial burden [19, 23, 24] and greater physical impairment [19, 25] especially when compared to non-carers.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, and although research has found contradictory findings [15], a large percentage of studies found that caring for a dependent person is related to a series of burdens that often takes them to their physical, psychological and emotional limits [1517], impacting the whole family system [15]. The responsibilities imposed by the caregiving situation may interrupt social life, activities or even work, which may be challenging [18]. For instance, some studies report that caregiving is usually associated with a deterioration in the quality of life [5, 6, 19, 20], higher levels of depression symptoms [5, 19, 21, 22], greater financial burden [19, 23, 24] and greater physical impairment [19, 25] especially when compared to non-carers.…”
Section: Introductionmentioning
confidence: 99%
“…The care activities provided by informal caregivers entail all kinds of activities related to the disease that the care recipient cannot perform alone due to the lack of personal autonomy because of the illness. This definition is widely used in the literature [25][26][27][28][29]. We used two questions to identify informal care: the first question asked whether the patients needed assistance due to the illness (does the patient need a carer to help with his/her daily activities (toilet, washing, dressing, helping him/her move, drug treatments, etc.)…”
Section: Methodsmentioning
confidence: 99%
“…Only in one country -the United Kingdom -do employers continue to contribute to the occupational pension on behalf on an employee during periods of care. In Sweden, while this is not mandatory, employers are encouraged to do so and most comply (OECD, 2011 [73]).…”
Section: Career Loss Compensation Provides a Forward-looking Vision Fmentioning
confidence: 99%